Optical and Printability Properties of 2-[[4-(Aminosulfonyl)- phenyl]hydrazono]-N-(4-ethoxyphenyl)-3-oxobutanamide - Oktav, Mehmet; Rollas, Sevim; N. Gencoglu, Efe (Asian Journal of Chemistry, 2010)
The synthesis and characterization of 2-[[4-(aminosulfonyl)phenyl]-hydrazono]-N-(4- ethoxyphenyl)-3-oxobutanamide (SM1) for a potential use in the formulations of printing inks were employed. Following this, SM1 was applied to an ink formulation and its printability together with densitometric and spectrophotometric colour values were examined by comparison with PY3 as a standard pigment. It was observed that the proposed dye had reasonable gloss, colour direction, transparency, mass colour, rub resistance, light fastness, densitometric and spectrophotometric values (CIE L* a* b*). These results indicated that the proposed compound could be used in oil based offset ink production as a pigment.